A dimensão pública da política de assistência social em um abrigo para pop-rua em Serra/ES : experiências de Apostar COM - Almeida, Bianca Batalha de (2017)
This project took place in a Night Shelter in Serra / ES, which comprises the services of Special Social Protection of High Complexity of Social Assistance, in the form of Institutional overnight welcoming, sheltering the adult population in street situation. The objective was to understand the public dimension of social assistance policy, that is, to pursue exactly what a given government policy benefits from meetings, connections, ties that produce transformative movements, the constitution of a more articulated body with a network known as movement. Starting from the conception of a body as interface between a subject and the world, it is proposed that its acquisition in the constitution of an analytical corpus would be done progressively through the availability for the unknown and the sensitivity to what the world is made of. Therefore, an investigation with homeless people known as ResearchWITH was carried out, using as instrumentsdevices the interview and the log from the institutional experience in the service. The narratives constituted in the meetings with four fellow participants were brought as experiences to be shared in specific locations and situations of a network, making each meeting, each connection each “way” matter. Thus, it is based on the intensification of experimentation and alliances, considering that through them questions may arise, which can forge a public social service that is experienced through the daily struggles in which the action with the other makes us resist the forces that prevent the movements of freedom of the processes of differentiation inherent in life.